Current Topics in Faecal Incontinence - Camilleri-Brennan, John (IntechOpen, 2020)
Faecal incontinence is a highly prevalent condition that continues to have an impact on the activities of daily living of both men and women worldwide. This book, Current Topics in Faecal Incontinence, provides a comprehensive and up-to-date overview of some specialist areas in the diagnosis and management of this condition. The topics that are discussed include the evaluation of faecal incontinence, quality of life, faecal incontinence in autoimmune disease and in obstructive defaecation, anal implants, and biosphincters. This book is an invaluable resource for physicians, surgeons, nurses, and allied healthcare professionals who seek to expand and refresh their knowledge in this field, as well as a source of excellent information for those preparing for professional examinations.